Ni-catalysed acceptorless dehydrogenative aromatisation of cyclohexanones enabled by concerted catalysis specific to supported nanoparticles - Takehiro Matsuyama; Takafumi Yatabe; Tomohiro Yabe; Kazuya Yamaguchi (Nature Communications)
Abstract The dehydrogenative aromatisation of cyclohexanone derivatives has had a transformative influence on the synthesis of aromatic compounds because functional groups can be easily introduced at desired positions via classic organic reactions without being limited by ortho-, meta- or para-orientations. However, research is still limited on acceptorless dehydrogenative aromatisation, especially with regard to nonprecious-metal catalysts. Ni is a promising candidate catalyst as a congener of Pd, but thermally Ni-catalysed dehydrogenative aromatisation has not been reported even in an oxidative manner because of the difficulty of β-hydride elimination and the fast re-insertion of Ni–H species. Here, we report a CeO2-supported Ni(0) nanoparticle catalyst for acceptorless dehydrogenative aromatisation of cyclohexanone derivatives. This catalyst is widely applicable to various compounds such as cyclohexanols, cyclohexylamines, N-heterocycles, enamines and β-heteroatom-substituted ketones. Through various experiments, we demonstrate that the present reaction was achieved by the concerted catalysis utilizing metal ensembles unique to supported metal nanoparticle catalysts.